2011
DOI: 10.1593/neo.101622
|View full text |Cite
|
Sign up to set email alerts
|

Neoplastic Transformation Induced by the gep Oncogenes Involves the Scaffold Protein JNK-Interacting Leucine Zipper Protein

Abstract: The activated mutants of the α-subunits of G proteins G(12) and G(13) have been designated as the gep oncogenes owing to their ability to stimulate diverse oncogenic signaling pathways that lead to neoplastic transformation of fibroblast cell lines and tumorigenesis in nude mice models. Studies from our laboratory as well as others have shown that the growth-promoting activities of Gα(12) and Gα(13) involve potent activation of c-Jun N-terminal kinases (JNKs). Our previous studies have indicated that the JNK-i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
15
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 32 publications
3
15
0
Order By: Relevance
“…Non-migrating cells on the proximal side of the inserts were removed with a cotton swab and the migrated cells on the distal side of the insert were fixed and stained with Hemacolor (EMD Chemicals, Inc., Gibbstown, NJ). To monitor invasive migration, similar procedures were carried out with the culture inserts (polyethylene terephthalate membrane with 8.0 μm pores #353097, BD Biosciences, Franklin Lakes, NJ), which were coated with rat-tail collagen, type 1 (BD Biosciences) as previously described 19 .…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Non-migrating cells on the proximal side of the inserts were removed with a cotton swab and the migrated cells on the distal side of the insert were fixed and stained with Hemacolor (EMD Chemicals, Inc., Gibbstown, NJ). To monitor invasive migration, similar procedures were carried out with the culture inserts (polyethylene terephthalate membrane with 8.0 μm pores #353097, BD Biosciences, Franklin Lakes, NJ), which were coated with rat-tail collagen, type 1 (BD Biosciences) as previously described 19 .…”
Section: Methodsmentioning
confidence: 99%
“…Immunoblot analyses with specific antibodies were carried out following our previously published procedures 19 . The following antibodies were used for immunoblot analyses.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The current study observed negative SPAG9 staining in normal bone tissues, and positive cytoplasmic SPAG9 expression in 63.8% (37/58) of osteosarcoma tissues, which was consistent with previous studies (19,. A number of studies have described the role of SPAG9 in cancer cell proliferation and provided accumulating evidence that characterizes SPAG9 as an oncoprotein regulating cell invasion. It was reported that SPAG9 siRNA knockdown inhibited cell invasion and proliferation in renal, lung and colorectal carcinoma (13,21,(23)(24)(25). To gain insight into the function of SPAG9 in osteosarcoma progression, SPAG9 expression was knocked down in the U2OS cell line and upregulated in the MG63 cell line in the present study.…”
Section: Discussionmentioning
confidence: 73%